A Material Purchasing Decision Making Model for Procurement Division of The Academic Library from Supply Chain Point View - Nurakmal Ahmad Mustaffa; Md. Mamun Habib; A. K. Mahbubul Hye (International Journal of Supply Chain Management, 2022)
The purpose of this study is to explore the development of the entities of a material purchasing decision making model for the procurement division of an academic library from a supply chain perspective and to describe the model's verification/validation procedure. Both qualitative and quantitative methodologies have been utilised in this study. Theoretical literature review was utilised to construct the conceptual model of the academic library, while Fuzzy Delphi Method (FDM) was employed to validate the model. This research will emphasise the functions and components necessary to design and validate the material purchase decision making model for the library's procurement division. The conclusion of this research will be the construction of a material purchasing decision making valid model for the procurement division of the academic library model, which will serve as a strategic tool to ensure a quality service for library users and stakeholders.